PENINGKATAN LITERASI KEUANGAN SEJAK DINI DAN PENGUATAN EKONOMI LOKAL BERBASIS SYARIAH DI PASAR RAWA - Istiaza Azra; Liza Asri; Ilham Anggiantoro; Fatimah Zahara (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Improving financial literacy from an early age and strengthening the local economy based on sharia values are strategic steps in building an independent and competitive society. The community service program in Pasar Rawa Village was carried out through three main activities, namely the Sharia Capital Market Investment and Financial Literacy Seminar with speakers from the Indonesia Stock Exchange and Maybank Sekuritas, education on understanding the rupiah and saving practices for elementary school students, and observation visits to bamboo craftsmen MSMEs. The seminar aimed to increase public understanding of halal investment and financial management in accordance with sharia principles. The education program in elementary schools focused on forming positive financial habits from an early age. Meanwhile, the SME visits were conducted to understand business conditions, introduce simple financial record-keeping, and introduce alternative sharia financing. The results of the activities showed an increase in knowledge, changes in financial attitudes, and growing interest among the community and SMEs in applying sharia financial principles.